Procedure-dependence and Tissue Factor-independence of Hypercoagulability during Orthopaedic Surgery - Fedi, S.; Gori, A. M.; Falciani, M.; Cellai, A. P.; Aglietti, P.; Baldini, A.; Vena, L. M.; Prisco, D.; Abbate, R.; Gensini, G. F. (Thrombosis and Haemostasis, 1999)
The increased risk for deep vein thrombosis (DVT) after orthopaedic surgery has been well documented as well as hypercoagulable state during both total hip arthroplasty (THA) and total knee replacement (TKR). To investigate the influence of the surgical procedure [postero-lateral (PL) or lateral (L) approach for THA, use of tourniquet (TQ) or not use of TQ for TKR] on the hypercoagulability and the role of extrinsic pathway activation and endothelial stimulation during orthopaedic surgery we have examined 40 patients (20 patients undergoing primary THA – 10 with PL approach and 10 with L approach – and 20 patients undergoing TKR – 10 with TQ application and 10 without TQ). Thrombin-antithrombin complexes (TAT), tissue factor (TF), tissue factor pathway inhibitor (TFPI), thrombomodulin (TM) and von Willebrand factor antigen (vWF:Ag) were analyzed before and during the orthopaedic surgery. During THA, TAT plasma levels increased more markedly in patients assigned to the L than PL approach (p <0.05); during TKR an elevation of TAT of higher degree (p <0.05) was observed when TQ was not applicated. Blood clotting activation was significantly (p <0.001) more relevant during THA than TKR. No changes in TF and vWF:Ag plasma levels were observed in all patients undergoing THA and TKR. TFPI plasma levels significantly (p <0.05) decreased 1 h after the end of the THA in group PL and group L, whereas they remained unaffected in the two groups of patients undergoing TKR. Similarly TM plasma levels significantly decreased during THA, but not during TKR. In conclusion, these results show that: 1) the site of surgical procedures and the type of approach affect the degree of hypercoagulability, 2) the blood clotting activation takes place in the early phases of orthopaedic surgery, without signs of extrinsic pathway and endothelial activation.